2004
DOI: 10.1111/j.0021-8782.2004.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the spermatozoon of the lizardIguana iguana(Reptilia, Squamata, Iguanidae) and the variability of sperm morphology among iguanian lizards

Abstract: The spermatozoon of Iguana iguana is filiform and resembles that of other iguanian lizards, being most similar to Tropidurus . All sperm synapomorphies of Tetrapoda, Amniota and Squamata are present in the sperm of Iguana iguana . By reconstructing the evolution of 30 sperm characters we identified a novel synapomorphy of Iguania: the presence of a well-developed acrosomal ridge at the level of the epinuclear lucent zone. Because of the poor topological resolution among iguanian clades we could not discount th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Besides that, the following spermatozoon synapomorphies of Serpentes are present in C. durissus ( Oliver et al, 1996 andJamieson, 1999): presence of dense collar, multilaminar membranes and extracellular tubules; reduction of the perforatorium base plate; and the unusual elongation of the midpiece. According to Jamieson (1995), Oliver et al (1996), Teixeira et al (1999), Giugliano et al (2002) and Vieira et al (2004), the spermatozoa ultrastructure is a relevant source of characters for use in phylogenetic analysis of Squamata, although the number of species for which the gamete ultrastructure is described must be augmented. Since descriptions concerning Serpentes spermatozoa are even scarcer, the present work may contribute to resolve phylogenetic relationships of this group in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides that, the following spermatozoon synapomorphies of Serpentes are present in C. durissus ( Oliver et al, 1996 andJamieson, 1999): presence of dense collar, multilaminar membranes and extracellular tubules; reduction of the perforatorium base plate; and the unusual elongation of the midpiece. According to Jamieson (1995), Oliver et al (1996), Teixeira et al (1999), Giugliano et al (2002) and Vieira et al (2004), the spermatozoa ultrastructure is a relevant source of characters for use in phylogenetic analysis of Squamata, although the number of species for which the gamete ultrastructure is described must be augmented. Since descriptions concerning Serpentes spermatozoa are even scarcer, the present work may contribute to resolve phylogenetic relationships of this group in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the morphological variability of spermatozoa, not only in the Serpentes but in members of the Squamata as a whole, can be associated with the reproductive characteristics of their species (Vieira et al, 2004), which are subject to a high degree of variation between one another such as: enzymes associated with the transport of sperm, sperm storage places in the female reproductive tract (Olsson et al, 1994, Almeida-Santos and Salomão, 1997, Blackburn, 1998and Server and Hamlett, 2002, fertilization process, place of fertilization (Blackburn, 1998), oviduct or sperm secretions for sperm maintenance in the female reproductive tract, and the mechanism of sperm release from storage regions (Girling, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the acrosome in the oscine spermatozoon possesses a lateral membrane evagination or projection, known as the helical membrane. 57 Jamieson et al 72 have suggested a different name for this structure, and made a case for the recognition of 2 parts of the oscine acrosome (discussed in detail later on in this section). The neck region has long been observed to contain only one centriole, the distal centriole,non-passerine birds.…”
Section: Oscine Spermatozoamentioning
confidence: 99%
“…These data have focused on morphological facets that may be beneficial in phylogenetic deduction because gamete ultrastructure has been considered a source for nontraditional character matrices. [1][2][3][4][5][6][7][8][9] However, given the large number of snake species, descriptions of spermatozoa ultrastructure in the Ophidia are still limited at best, 10 and complete descriptions of the entire process of spermiogenesis within snakes are rare., 9,10 There are a few reports that focus on specific parts of spermiogenesis in snakes, [11][12][13][14][15] but to our knowledge the only comprehensive spermiogenic study in ophidians that describes the complete ultrastructural ontogeny of acrosome development, flagellar formation, elongation, and condensation of the spermatid DNA concerned the Cottonmouth (Agkistrodon piscivorus), 10 which is a member of the Viperidae. There also exists a comparative account of spermiogenesis ultrastucturally between Agkistrodon contortrix (though incomplete for the Copperhead) and its sister taxon A. piscivorus, 9 and an earlier study that determines all the major events of spermatid development in the Rock Python, Python sebae.…”
Section: Introductionmentioning
confidence: 99%